Parametric Optimization in Photochemical Machining of Aluminium Using Taguchi Method. (March 2019) - Mazarbhuiya, Rashed Mustafa; Rahang, Maneswar
Abstract: The objective of this study was to investigate the optimal process parameters of photochemical machining on aluminium workpiece. The input parameters considered were etching concentration, etching temperature and etching time. The study revealed their effects over Material Removal Rate, Surface Roughness and Edge Deviation. L9 Taguchi design was used to formulate the experimental layout. ANOVA and average S/N ratio were performed for the optimal setting of the process parameters. For larger-the-better characteristics the optimal conditions for MRR was obtained at etching concentration of 600g/L, etching temperature of 60°C and etching time of 8 minutes. For, smaller-the-better characteristics, the optimal setting for surface roughness was obtained at etching concentration of 400g/L, etching temperature of 40°C and etching time of 4 minutes and for edge deviation obtained at etching concentration of 400g/L, etching temperature of 40°C and etching time of 8 minutes.